Analisis Strategi Pemasaran Untuk Meningkatkan Penjualan Minuman Kedai Kopi Square di Kota Bandar Lampung - Yuliana, Yuliana; Ardansyah, Ardansyah (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
This Square Coffee Shop is located on Wolter Monginsidi Street No.50 Bandar Lampung City. This study reviews the problem of Marketing Strategy Analysis in Beverage Sales at the Square Coffee Shop in Bandar Lampung City. The type of researcher used is a qualitative method using interview techniques, and documentation is carried out in order to obtain information or reports through business owners and employees. The essence of this research is how to analyze the marketing strategy in increasing the sales of beverages at the Square Coffee Shop in Bandar Lampung City? The research shows that management regarding marketing strategy includes: 1) Segmentation, 2) Targeting, 3) Positioning, and 4) Marketing Mix. The results are quite reliable, namely: Applying Marketing Strategies in improving current marketing both in not determining segmentation, targeting, positioning, and marketing mix which can then increase sales and income.